2021
DOI: 10.36764/jc.v5i1.555
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Media Pembelajaran E-Learning Terhadap Hasil Belajar Mahasiswa Prodi PGSD Universitas Quality Berastagi

Abstract: With this era of increasingly developing technology, learning programs are directed to be able to make better use of technology. One of the current uses of technology is e-Learning using the web to access it. There is no denying that many students now have smart phones, so it is easier to access them from wherever they are and at any time. Utilization of e-learning that is commonly developed today is using LMS (Learning Management System). Quality Berastagi University is one of the universities that have utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Keterampilan penalaran ilmiah siswa dapat meningkat dengan menggunakan CBL (Andini et al, 2023;Ichsan et al, 2018;Wati & Sunarti, 2019), kemampuan berpikir kritis (Alfiandra et al, 2022) serta meningkatkan motivasi dan partisipasi siswa (Arianto & Fauziyah, 2020b). Kemudian, melalui CBL hasil pembelajaran praktikum sistem pencernaan meningkat (Aulia et al, 2023) dan juga hasil belajar mahasiswa (Simbolon, 2022). Hasil penelitian ini memberikan kontribusi ilmiah dan memperkuat pemahaman tentang bagaimana CBL dapat digunakan secara efektif dalam meningkatkan kemampuan siswa di tingkat pendidikan dasar khususnya siswa kelas V sekolah dasar.…”
Section: Gambar 1 Percobaan Untuk Merencanakan Investigasi Kasusunclassified
See 1 more Smart Citation
“…Keterampilan penalaran ilmiah siswa dapat meningkat dengan menggunakan CBL (Andini et al, 2023;Ichsan et al, 2018;Wati & Sunarti, 2019), kemampuan berpikir kritis (Alfiandra et al, 2022) serta meningkatkan motivasi dan partisipasi siswa (Arianto & Fauziyah, 2020b). Kemudian, melalui CBL hasil pembelajaran praktikum sistem pencernaan meningkat (Aulia et al, 2023) dan juga hasil belajar mahasiswa (Simbolon, 2022). Hasil penelitian ini memberikan kontribusi ilmiah dan memperkuat pemahaman tentang bagaimana CBL dapat digunakan secara efektif dalam meningkatkan kemampuan siswa di tingkat pendidikan dasar khususnya siswa kelas V sekolah dasar.…”
Section: Gambar 1 Percobaan Untuk Merencanakan Investigasi Kasusunclassified
“…Gap penelitian dalam penelitian ini fokus pada penerapan CBL untuk pembelajaran di tingkat dasar, khususnya pada siswa kelas V SD Muhammadiyah 1 Krian. (Simbolon, 2022). Selain itu penelitian lainnya mendapatkan hasil bahwa model Pembelajaran Case Based Learning (CBL) berbasis HOTS sangat baik bagi siswa karena model pembelajaran tersebut bersifat inovatif dan dapat menstimulus siswa lebih aktif dalam penyelesaian suatu permasalahan (Arianto & Fauziyah, 2020a).…”
unclassified
“…The results of data grouping on variables measured using the case-based learning (CBL) model found that the implementation of the case-based learning (CBL) model can improve student learning outcomes, namely as many as four articles. The four articles were successively written byAsfar et al (2019),Kamarudin (2023),Simbolon (2022), and Wospadrik et al (2020).Furthermore, there are two articles stating that the implementation of the case-based learning (CBL) model affects students' concept understanding in certain materials, including in mathematics learning materials also written byAsfar et al (2019) and understanding the concept of petroleum material written by Citra Ayu Dewi and Abdul Hamid (2020). In addition, the implementation of the case-based learning (CBL) model can also improve students' critical thinking skills, this is based on the results of four articles written by Aisy Ghina Rihadatul and Hidayati Nani (2022), Siti Nur Rohmah and Mukhayyarotin Niswati Rodliyatul Jauhariyah (2020), Ni Putu Irma Dharmayanthi (2022), Kusumawati et al (2019).…”
mentioning
confidence: 99%